NАTURАL - HISTОRICАLАSРЕCTSОFРRОDUCTIОNОFSАCRЕDLАNDSCАРЕS (Scientific journal of the Fergana State University, 2024)
The article describes the emergence of dual concepts about sacred territories, sacred places and the origin of sacred landscapes. The formation of sacred landscapes of sacred places, their performance of various functions as shrines, tendencies of sacralization of territories, natural and historical factors in the location of sacred landscapes are analyzed.